Artemisia annua – Importance in Traditional Medicine and Current State of Knowledge on the Chemistry, Biological Activity and Possible Applications - Ekiert, Halina; Świątkowska, Joanna; Klin, Paweł; Rzepiela, Agnieszka; Szopa, Agnieszka (Planta Medica, 2021)
Artemisia annua (annual mugwort) is a species that has long been used in traditional Asian medicine, mainly Chinese and Hindu. The species is widespread and known as a medicinal plant not only in Asia but also in Europe, in both Americas, and Australia. The species has become a subject of particular interest due to the 2015 Nobel Prize awarded for detecting the sesquiterpene lactone artemisinin in it and proving its antimalarial activities. The raw materials obtained from this species are Artemisiae annuae folium and Artemisiae annuae herba. The leaves are a raw material in the Chinese Pharmacopoeia and Vietnamese Pharmacopoeia. Both raw materials are in the International Pharmacopoeia published by the WHO. The main components of these raw materials are mainly specific sesquiterpene lactones, essential oil, flavonoids, coumarins, and phenolic acids. In traditional Asian medicine, the species is used, for example, in the treatment of jaundice and bacterial dysentery, as an antipyretic agent in malaria and tuberculosis, in the treatment of wounds and haemorrhoids, and in viral, bacterial, and autoimmune diseases. Professional pharmacological studies conducted today have confirmed its known traditional applications and explain previously unknown mechanisms of its biological action and have also found evidence of new directions of biological activity, including, among others, anti-inflammatory, analgesic, antioxidant, antitumour, and nephroprotective activities. The species is of growing importance in the cosmetics industry.
Keywords: Artemisia annua; Asteraceae; annual mugwort; qinghao